2023
DOI: 10.3390/toxins15040284
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Pain Evaluation in Response to OnabotulinumtoxinA for Chronic Migraine: An Observational Real-Life Study

Abstract: (1) Background: Randomized controlled trials and real-life studies demonstrated the efficacy of OnabotulinumtoxinA (OBT-A) for CM prevention. However, no studies specifically addressed its effect on pain’s quantitative intensity and qualitative characteristics. (2) Methods: This is an ambispective study: a post-hoc retrospective analysis of real-life prospectively collected data from two Italian headache centers on CM patients treated with OBT-A over one year (i.e., Cy1-4). The primary endpoint was the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
2
1
Order By: Relevance
“…The BoNT-A group showed a smaller reduction of HIT-6 score at 6 and 12 months compared to anti-CGRP mAbs, which, however, was at the limit of clinical relevance. Our data conflicts with other experiences in the literature that showed a slightly superior mean reduction of HIT-6, being at least 5 points or even more [ 38 , 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The BoNT-A group showed a smaller reduction of HIT-6 score at 6 and 12 months compared to anti-CGRP mAbs, which, however, was at the limit of clinical relevance. Our data conflicts with other experiences in the literature that showed a slightly superior mean reduction of HIT-6, being at least 5 points or even more [ 38 , 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, due to the connection between the decrease in headache intensity and disability scales, conducting a thorough headache assessment with patient-reported outcome measures (PROMs), beyond tracking headache days, is advised for a more accurate evaluation of treatment response in chronic migraine. However, only some real-world studies have specifically examined the impact of onabotulinumtoxinA on the qualitative aspects of headache pain in treated individuals (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…They have also shown that treatment with OBT-A decreases disability and improves patients’ quality of life, as measured by standardized scales [ 20 ]. However, for pain syndromes (such as migraine), other non-quantifiable aspects must be considered [ 23 ].…”
Section: Introductionmentioning
confidence: 99%